Neither dupes, nor pipers: violent crime, public sentiment and the political origins of mass incarceration in the United States - Cheliotis, Leonidas (2020)
One of the most contentious questions in contemporary penology is why the use of imprisonment started rising rapidly in the United States in the early 1970s. The two dominant perspectives on the subject focus on crime's public salience and how it relates to violent crime and political elites, respectively. The first perspective holds that incumbent political elites promoted tougher criminal justice policies in the name of a public concern about violent crime that they previously aroused themselves, in order ultimately to serve narrow interests. The second perspective argues instead that politicians in office toughened criminal justice policies in response to a legitimate public disquiet about violent crime. Based on an unprecedented comparison of trends in violent crime and public opinion over the period 1960–1980, this article suggests that both perspectives misread how the politics of crime and criminal justice unfolded around the time mass incarceration was taking off. Research on the subject should henceforth shift its focus onto perspectives that do not treat majority public opinion as a key element in criminal justice policy-making